EVALUASI TEPAT PASIEN, TEPAT OBAT, DAN TEPAT DOSIS PENGGUNAAN ANTIPSIKOTIK PASIEN SKIZOFRENIA DI RUMAH SAKIT JIWA PROVINSI NTB - Ni Komang Wijiani Yanti; Dwi Andayani (Jurnal Insan Farmasi Indonesia, 2021)
One of the mental disorders caused by the inability of individuals to make adjustments is schizophrenia. Schizophrenia is a chronic and severe disorder that affects a person thinks, feels, and acts. The management of schizophrenia treatment one of which uses antipsychotics. Evaluation parameters include the right drug, right dose, right patient, and right frequency of drug use. This research is a descriptive with data collection retrospectively. Data collection was carried out by using purposive sampling method by looking at the medical record data of inpatient schizophrenia in the period of January - December 2019 as many as 87 medical records. Schizophrenia was more experienced by men (79.31%) and aged 26-35 years (56.32%). The most common type of schizophrenia is paranoid as many as 75 patients (86.21%). The most common use of antipsychotics is the typical + atypical antipsychotic combination group of 44 patients (50.57%). The evaluating the accuracy of the use of antipsychotics obtained 88.51% right of the drug; 100% right patient; 98.85% correct dosage; and 96.55%% exact frequency. The use of drugs during hospitalization is good, but evaluation and monitoring are needed because there are still inaccuracies in the drug, dosage, and frequency in the use of antipsychotic drugs.